2022
DOI: 10.3389/fmed.2021.824239
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Foveal Outer Nuclear Layer of Central Serous Chorioretinopathy Patients Over the Disease Course and Their Response to Photodynamic Therapy

Abstract: Objective:To investigate the association between foveal outer nuclear layer (ONL) thickness and the natural course of central serous chorioretinopathy (CSC), as well as the thickness change after photodynamic therapy (PDT), exploring the PDT timing for CSC.Methods:This retrospective consecutive case series included 358 CSC patients between January 2014 and December 2019. All patients were divided into four groups depending on disease duration: Group A: ≤1 month; Group B: >1 and ≤3 months; Group C: &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The thinner the ONL and the lower the BCVA, the higher the incidence of EZ- [ 26 ]. Mingwei Zhao et al [ 27 ] believed that the thinning of foveal ONL was positively correlated with the course of CSC, and the longer duration of disease limited the recovery of foveal ONL. ONL is composed of pyramidal cell bodies, so the decrease of ONL thickness indicates that the number of pyramidal cells decreases.…”
Section: Discussionmentioning
confidence: 99%
“…The thinner the ONL and the lower the BCVA, the higher the incidence of EZ- [ 26 ]. Mingwei Zhao et al [ 27 ] believed that the thinning of foveal ONL was positively correlated with the course of CSC, and the longer duration of disease limited the recovery of foveal ONL. ONL is composed of pyramidal cell bodies, so the decrease of ONL thickness indicates that the number of pyramidal cells decreases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, changes in central macular thickness and subfoveal choroidal thickness were associated to the resolution of CSCR, while the amount of SRF to the visual acuity outcomes. Moreover, the morphology of the retinal layers, such as ONL thinning, PR layer elongation, ELM and ellipsoid zone disruption was previously associated with longer duration of SRF and worse visual acuity [17,28,29].…”
Section: Discussionmentioning
confidence: 98%
“…[21][22][23] In a retrospective study on 358 patients with CSC, ONL thinning was found to be proportional to disease duration, with more pronounced differences detected after a disease duration of 6 months. 24 Piccolino et al categorized the eyes of CSC patients with PR layer elongation, which is a stretch of PR length, including the external limiting membrane, the ellipsoid zone, and the interdigitation zone because of SRF in two subgroups: the first group with a preserved anatomy of the outer retinal layers, associated with a better long-term visual prognosis, and a second group, characterized by atrophic changes in the PR layer and poorer visual outcomes. 25 In a recent study, a thinning of the PR layer above the point of focal leakage on fluorescein angiography was found in patients with aCSC as a sign of mild outer retina atrophy.…”
Section: Discussionmentioning
confidence: 99%